Influence of the processing variables on the microstructure and properties of gelatin‐based scaffolds by freeze‐drying. Issue 25 (23rd February 2019) - Perez‐Puyana, V.; Felix, M.; Romero, A.; Guerrero, A.
ABSTRACT: In the last few years, the field of tissue engineering has suffered an exponential growth, and although it is true that the processing parameters affect the properties of the scaffolds, only a few studies have investigated that statement. For that reason, the influence of different parameters involved in the freeze‐drying process (container, freezing temperature, pH, and solvent used) on the mechanical and structural properties of gelatin‐based scaffolds was analyzed in this study. Thus, rheological measurements and porosity analyses were performed to evaluate the scaffolds obtained. Results indicate that the parameters evaluated modify the mechanical properties of the scaffold, highlighting the option of a plastic mold to contain an acidic protein solution produced using a weak acid (acetic acid) at low concentration (0.05 M) as solvent. On the contrary, only the pH and the freezing temperature led to significant differences in the porosity of these scaffolds, obtaining values higher than 95% for all the systems studied. These results are useful to demonstrate that the control of the different parameters implied in the processing technique allows designing a scaffold with specific properties suitable for different applications. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47671. Abstract :